1952
DOI: 10.1002/jlac.19525750106
|View full text |Cite
|
Sign up to set email alerts
|

Protofagopyrin und Fagopyrin, die photodynamisch wirksamen Farbstoffe des Buchweizens (Fagopyrum esculentum)

Abstract: B r o c k m a n n , W e b e r und P a m p u s 53 2, L. JIcrian, Zeitschr. f. Anat. Physiol. 1915, 161. 3, Mitt. Finscns Jlcdicinske Lysinstitut 9, 103 (1005). ') Als photodynamischen Effekt bezeichnet man nwli tlcm Vorschlag seincar Entdecker H. v. T a p p c i n o r und A. J o d l b a u e r allgemcin die Photosonsibilisierung lebcnder Zellen durch fluorescicrendo Farbstoffe. Die Scnsibilisicrung hohercr Ticrc ist also nur ein Spezialfall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1952
1952
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…1, fagopyrin is an analog of hypericin with two piperidine side chains. It is reported that fagopyrin can be hydrolysed to hypericin (13). However, we were unable to degrade the buckwheat extract in a similar manner.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…1, fagopyrin is an analog of hypericin with two piperidine side chains. It is reported that fagopyrin can be hydrolysed to hypericin (13). However, we were unable to degrade the buckwheat extract in a similar manner.…”
Section: Discussionmentioning
confidence: 53%
“…The potent PK inhibitory activity exhibited by hypericin (7, 8) prompted our search for other hypericin-like compounds. We started ex- To compare the extract we had obtained with the fagopyrin characterized by Brockmann, we extracted buckwheat according to the method described by Brockmann (13). The extract so obtained also resolved into 3 major red fluorescent bands on TLC with some impurities staying at the base.…”
Section: Discussionmentioning
confidence: 99%
“…Flowers are a superior extraction material compared to other plant parts due to their higher fagopyrin content and lower chlorophyll levels. Currently, the most efficient isolation method is an HPLC method, which enables the full separation 21 Brockmann 22 Hinneburg 33 Eguchi 25 Hagels 58 Tavcǎr Benković2 0 fagopyrin A fagopyrin B fagopyrin C acetone − + − +++ ++++ acetone/pyridine (9:1) + acetone/water (9:1) and (4:1) + acetone/water/acetic acid (8:1:1) (1:9) with 0.5% acetic acid was further purified using styrene divinylbenzene copolymer CC with water/methanol gradients; fagopyrins were eluted using methanol with 0.5% acetic acid and further purified on Sephadex LH 20 CC that was eluted with dichloromethane/acetone/methanol (5:3:2); yellow fractions that comigrated with the red fluorescent compounds in the silica gel were successfully removed using Dianion Benković2 0 prior removal of chlorophylls with dichloromethane, then extraction at 60°C by ultrasound in acetone/water (9:1); HPLC separation and fraction collection according to the method described underAnalytical Methods isolation of individual fagopyrin, with impurities of other fagopyrins of fagopyrins from other compounds. However, an analytical system was used, which did not allow a sufficient quantity of fagopyrins to be obtained for weight determination.…”
Section: ■ Isolation Attemptsmentioning
confidence: 99%
“…Common buckwheat originates from Southwest China and it has been gradually spread to other continents (Kreft 1995). Buckwheat contains fagopyrins, phototoxic naphtodianthrones, similar to hypericin (Brockmann et al 1952). The highest levels of fagopyrins were determined in flowers and leaves .…”
Section: Vsebnost Fagopirina In Rutina V Semenih Navadne Ajde Tretiramentioning
confidence: 99%